Prevalence of haemoglobin A1c based dysglycaemia among adult community dwellers in selected states in Nigeria: a descriptive cross-sectional study - Ajayi, Ikeoluwapo O.; Balogun, William O.; Olopade, Oluwarotimi B.; Ajani, Gbadebo O.; Soyoye, David O.; Bolarinwa, Oladimeji A.; Olamoyegun, Michael A.; Alatishe-Muhammad, Bilqis W.; Odeniyi, Ifedayo A.; Odukoya, Olukemi; Fasanmade, Olufemi A.; Diyaolu, Funmilayo P.; et al. (Frontiers in Endocrinology, 2023)
Background: Type 2 Diabetes Mellitus (T2DM) is a disease of public health importance globally with an increasing burden of undiagnosed pre-diabetes and diabetes in low and middle income countries, Nigeria inclusive. Pre-diabetes and diabetes are established risk factors for cardiovascular complications. However, data is scanty on the current prevalence of these conditions in Nigeria, based on HbA1c diagnosis as recommended by the WHO since 2009. We aimed to determine the prevalence of pre-diabetes, diabetes and undiagnosed diabetes among adult population of Nigeria using HbA1c. Methodology: A cross-sectional, multi-site population study was carried out in selected states in Nigeria: Ekiti, Lagos, Osun, Oyo and Kwara States involving 2,708 adults (≥18 years) rural and urban community dwellers, without prior diagnosis of prediabetes or diabetes. Participants with ongoing acute or debilitating illnesses were excluded. Data were collected using an interviewer administered pretested, semi-structured questionnaire. Socio-demographic, clinical (weight, height, blood pressure, etc) and laboratory characteristics of participants including HbA1c were obtained. Data were analyzed using STATA version 16. Results The mean age of participants was 48.1±15.8 years and 65.5% were females. The overall prevalence of prediabetes and undiagnosed diabetes were 40.5% and 10.7% respectively while prevalence of high blood pressure was 36.7%. The prevalence of prediabetes and diabetes were highest in Lagos State 29.7% and 25.2% respectively. Independent predictors of diabetes and prediabetes include excess weight gain, sedentary living and ageing. There was significant association between age of the participants (p<0.001), gender (p=0.009), educational status (p=0.008), occupation (p<0.001), tribe (p=0.004), marital status (p<0.001), blood pressure (p<0.001), and their diabetic or prediabetic status. Participants within the age group 45-54 years had the highest total prevalence (26.6%) of prediabetes and diabetes, 56.2% of which had high blood pressure. No participant within the age range ≤24years had diabetes. Conclusion Over half of respondents had prediabetes and diabetes with a high prevalence of undiagnosed diabetes. A nationwide screening campaign will promote early detection of prediabetes and undiagnosed diabetes among adult Nigerians. Health education campaigns could be an effective tool in community settings to improve knowledge of the risk factors for diabetes to reduce prevalence of dysglycaemia.